Modulation of interleukin-23 signaling with guselkumab in biologic-naive patients versus tumor necrosis factor inhibitor–inadequate responders with active psoriatic arthritis - Siebert, S; Coates, LC; Schett, G; Raychaudhuri, SP; Chen, W; Gao, S; Seridi, L; Chakravarty, SD; Shawi, M; Lavie, F; Sharaf, M; Zimmermann, M; et al. (Wiley, 2024)
Objective We assessed and compared immunologic differences and associations with clinical response to guselkumab, a fully human interleukin (IL)–23p19 subunit inhibitor, in participants with active psoriatic arthritis (PsA) who were biologic-naive or had inadequate response to tumor necrosis factor inhibitors (TNFi-IR).